Amnion Membrane Graft Dressing in Superficial Partial Thickness Burn in Pediatric Patients - Ullah, Md Saif; Ferdous, KMN; Mullick, Md Mobassar Hussain; Alam, Md Rashedul; Rahman, Md Sazzaduar; Khan, AR (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Objective: The aim of this study was to find out the effectiveness of amniotic membrane graft dressing in the treatment of superficial partial thickness burn in children. Methods: The retrospective study was conducted on the patients admitted with superficial partial thickness burn in the burn unit of Dhaka Shishu Hospital age 0-12 years, during the period from January 1999 to December 2011. All of them treated with amnion membrane graft dressing. Results: Total 370 patients were included in this study. Mean age was 2.76 years. Amnion dressing suppresses bacteria in the wound as well as reduced infection. Amnions have good adherent characteristics, which reduced infection as well as reduction of oozing of plasma from the wound, that become dry early. It has a role on burnt pain reduction, Frequency of dressing change, rate of healing, cost, duration hospital stay. Conclusion: Our experience showed that amniotic membrane is one of the effective biological skin substitutes used in burn wounds, with efficacy of low bacterial counts, has advantageous of reducing protein loss, electrolytes & fluids. Decreasing the risk of infection minimizing pain, accelerate of wound healing and good handling properties. It is ready available does not present immunological problem and allergies response. It is cost effective and very helpful for developing countries. DOI: http://dx.doi.org/10.3329/cmoshmcj.v14i1.22875 Chatt Maa Shi Hosp Med Coll J; Vol.14 (1); Jan 2015; Page 22-25